PERCEPTION OF ENTREPRENEURS REGARDING BUSINESS ENVIRONMENT IN MONTENEGRO: REGIONAL ANALYSIS - Bojan Lekovic; Slobodan Maric; Sandra Djurovic; Nemanja Berber (European Scientific Journal, ESJ, 2014)
The goal of this work is to analyze the economic ambient by entrepreneurs through the identification of the most significant barriers exerting influences on the development of business in Montenegro. For the needs of researching, the questionnaire was created consisting of 30 questions, including five groups of barriers. The questionnaire was filled in by 102 business people with their main offices in Montenegro. Collected data were processed by means of the statistical processing data program SPSS20. The descriptive analysis was used with a view of getting the hierarchy of observed barriers, while the one-way analysis of variance (ANOVA) was used for determining statistically significant differences regarding to observed barriers by entrepreneurs classified into three geographical regions (maritime, central and northern). Financial resources, procedures in the local competence and centralized procedures were recognized by entrepreneurs as barriers of the greatest importance on entrepreneurial development. Statistically significant differences between the observed barriers by entrepreneurs in three geographical regions appeared in case of development inequality of regions and administrative procedures in employment.